Study and Test on Energy-Saving Technology of Optical Access Network - Yan Jiang; Zhanhai Zhuang (Dianxin kexue)
According to the energy consumption status and network characteristics of the optical access network，the energy consumption distribution and the main factors that could affect energy consumption in optical access network environment were analyzed. Based on the analysis，energy-saving method of equipments and new technology of energy-saving and optical access network were researched，and then，laboratory test was developed. All of these could provide credible theory and experience for green optical access network application.